Customer order fulfilment in mass customisation context - an agent-based approach. (2015) - Medini, Khaled
The ever increasing customer specific needs require suitable strategies to accommodate his requirements and deliver exactly what he wants and in due course. Mass customisation, as a successor of mass production is one of these strategies, it aims at satisfying customer needs with near mass production efficiency. However, achieving efficiency is challenged by several issues such as customer order fulfilment in a customisation environment. In fact, product variety induced by customer choices requires flexible production systems able to manage internal complexity caused by such external variety. This paper proposes a multi-agent-based model to manage customer orders by: 1) defining production requirements of each order; 2) simulating the execution of the production and delivery operations. It then illustrates the proposed model with a case study and investigates the impact of inventory management on the enterprise economic performance. The case study shows how the model supports the decision-making process with respect to customer order fulfilment.